A New Dermal Substitute Containing Polyvinyl Alcohol with Silver Nanoparticles and Collagen with Hyaluronic Acid: In Vitro and In Vivo Approaches - Dario Mendes Júnior; Moema A. Hausen; Jéssica Asami; Akemi M. Higa; Fabio L. Leite; Giovanni P. Mambrini; Andre L. Rossi; Daniel Komatsu; Eliana A. de Rezende Duek (MDPI AG, 2021)
The experimental use of poly (alcohol-vinyl) (PVA) as a skin curative is increasing widely. However, the use of this hydrogel is challenging due to its favorable properties for microbiota growth. The association with silver nanoparticles (AgNPs) as an antimicrobial agent turns the match for PVA as a dressing, as it focuses on creating a physical barrier to avoid wound dehydration. When associated with extracellular components, such as the collagen matrix, the device obtained can create the desired biological conditions to act as a skin substitute. This study aimed to analyze the anti-microbiological activity and the in vitro and in vivo responses of a bilaminar device of PVA containing AgNPs associated with a membrane of collagen-hyaluronic acid (col-HA). Additionally, mesenchymal stem cells were cultured in the device to evaluate in vitro responses and in vivo immunomodulatory and healing behavior. The device morphology revealed a porous pattern that favored water retention and in vitro cell adhesion. Controlled wounds in the dorsal back of rat skins revealed a striking skin remodeling with new epidermis fulfilling all previously injured areas after 14 and 28 days. No infections or significant inflammations were observed, despite increased angiogenesis, and no fibrosis-markers were identified as compared to controls. Although few antibacterial activities were obtained, the addition of AgNPs prevented fungal growth. All results demonstrated that the combination of the components used here as a dermal device, chosen according to previous miscellany studies of low/mid-cost biomaterials, can promote skin protection avoiding infections and dehydration, minimize the typical wound inflammatory responses, and favor the cellular healing responses, features that give rise to further clinical trials of the device here developed